2011
DOI: 10.1111/j.1463-1318.2011.02689.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oral polyethylene glycol plus a large volume glycerine enema with a large volume glycerine enema alone in patients undergoing colorectal surgery for malignancy: a randomized clinical trial

Abstract: A single large-volume glycerine enema is effective bowel preparation before colorectal resection whether performed by an open or minimally invasive technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…published a randomized control trial comparing the use of MBP plus glycerine enema and glycerine enema alone in patients undergoing laparoscopic colonic resections. There was no significant difference in terms of surgical site infection and anastomotic leakage rate observed between the two groups [12] .…”
Section: Discussionmentioning
confidence: 67%
“…published a randomized control trial comparing the use of MBP plus glycerine enema and glycerine enema alone in patients undergoing laparoscopic colonic resections. There was no significant difference in terms of surgical site infection and anastomotic leakage rate observed between the two groups [12] .…”
Section: Discussionmentioning
confidence: 67%
“…Most studies used an open approach to CRS except for 2 studies 38,39 using a laparoscopic approach and 4 studies 18,21,33,49 reporting on data from a mix of open and laparoscopic procedures. Quality appraisal of included RCTs is summarized in eTable 1 in the Supplement.…”
Section: Resultsmentioning
confidence: 99%
“…17,18,23,25,27,28,30,31,33,53,54 In contrast, Bretagnol et al, 21 Contant et al, 24 and Platell et al 29 reported a lower risk of infectious complications with MBP. Bucher et al 22 and Santos et al 32 reported increased morbidity and infectious complications, respectively, with MBP.…”
Section: Discussionmentioning
confidence: 97%
“…11 Glycerin has been well used and well studied in retrograde enemas and suppositories. 1416 Overall, glycerin has a rather safe side effect profile, especially relative to other commonly used enema solutions. One histological comparison of rectal mucosa in rats subjected to either glycerin or phosphate enema demonstrated less irritation with glycerin.…”
Section: Discussionmentioning
confidence: 99%